Regulating DNA Self‐assembly by DNA–Surface Interactions. (9th November 2017) - Liu, Longfei; Li, Yulin; Wang, Yong; Zheng, Jianwei; Mao, Chengde
Abstract: DNA self‐assembly provides a powerful approach for preparation of nanostructures. It is often studied in bulk solution and involves only DNA–DNA interactions. When confined to surfaces, DNA–surface interactions become an additional, important factor to DNA self‐assembly. However, the way in which DNA–surface interactions influence DNA self‐assembly is not well studied. In this study, we showed that weak DNA–DNA interactions could be stabilized by DNA–surface interactions to allow large DNA nanostructures to form. In addition, the assembly can be conducted isothermally at room temperature in as little as 5 seconds. Abstract : Help from the surface : DNA self‐assembly can be modulated by DNA–surface interactions that, in turn, can be readily tuned by metal ions. This allowed us to gain another layer of control over DNA self‐assembly for preparation of DNA nanostructures.